Vascularized Bone Grafts in Spinal Reconstruction: An Overview of Nomenclature and Indications - Skochdopole, Anna J.; Wagner, Ryan D.; Davis, Matthew J.; Raj, Sarth; Winocour, Sebastian J.; Ropper, Alexander E.; Xu, David S.; Bohl, Michael A.; Reece, Edward M. (Seminars in Plastic Surgery, 2021)
Several vascularized bone grafts (VBGs) have been introduced for reconstruction and augmenting fusion of the spine. The expanding use of VBGs in the field of spinoplastic reconstruction, however, has highlighted the need to clarify the nomenclature for bony reconstruction as well as establish the position of VBGs on the bony reconstructive algorithm. In the current literature, the terms “flap” and “graft” are often applied inconsistently when describing vascularized bone transfer. Such inconsistency creates barriers in communication between physicians, confusion in interpreting the existing studies, and difficulty in comparing surgical techniques. VBGs are defined as bone segments transferred on their corresponding muscular attachments without a named major feeding vessel. The bone is directly vascularized by the muscle attachments and unnamed periosteal feeding vessels. VBGs are best positioned as a separate entity in the bony reconstruction algorithm between nonvascularized bone grafts (N-VBGs) and bone flaps. VBGs offer numerous advantages as they supply fully vascularized bone to the recipient site without the microsurgical techniques or pedicle dissection required for raising bone flaps. Multiple VBGs have been introduced in recent years to optimize these benefits for spinoplastic reconstruction.
Keywords: bone graft; vascularized bone graft; bone flap; spine reconstruction; bone reconstruction; spinal fusion